REFLECTION OF CHARACTERS OF THE MASCULINITY OF MAIN CHARACTER IN TARUNG SARUNG MOVIE - Chalimah, Chalimah; Rahmabin, Alfiansyah; Qahar, Jabbar Abdulrahman (Universitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2024)
The analysis of masculinity in this movie uses Barthes semiotics theory. The researchers conduct masculinity research because it raises the phenomenon of heinous persecution based on defending his lover. The aim of this research is first to comprehend the characteristics of masculinity in terms of denotative, connotative, and myth of the main character in the movie Tarung Sarung. The method used in this research is a qualitative descriptive method with a semiotic model. The results of the research conclude that first, there are seven characteristics of the main character's masculinity found in this research, namely Physical; Deni Ruso has a handsome physique and courage, Functional; Deni Ruso helps people around him and his family, Sexual Aggressive; Deni Ruso wants to apologize and express feelings, Emotional; Deni Ruso can control emotions, Intellectual; Deni Ruso is not careless in making decisions, Interpersonal; Deni Ruso being able to become a leader in his environment and Personal Characteristics; Deni Ruso as a man who is financially successful. Semiotics helps analyze the implied meaning of the gradual process of forming masculine characters by supporting the theory of masculinity characteristics applied in this research. So, guidelines are found to form masculine attitudes and characters for every man.